Groundwater quality of Malawi : fluoride and nitrate of the Zomba-Phalombe plain - Von Hellens, Anastasia (SLU/Dept. of Soil and Environment, 2013)
Contamination of groundwater is a widespread issue around the globe and the water quality is highly dependent on the geology as well as anthropogenic interventions in the area. High (0.9 – 1.2 mg F-/L) fluoride levels in groundwater can give rise to dental fluorosis and have been reported in several areas of Malawi. Further studies of groundwater contamination apart from fluoride are limited. The aim of this study was to investigate the fluoride and nitrate concentrations of groundwater in boreholes around Lake Chilwa and the origin of the contaminants. The hypothesis was that elevated concentrations of fluoride and low nitrate concentrations would be found in the area.